The extent of commitment of Jordanian banks to apply internal control procedures to detect and prevent money laundering operations - Al-kasswna, Reem Okab (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aims at demonstrating the role and importance of internal control measures in combating money laundering operations in Jordanian banks through the statement of internal control procedures that contribute to the discovery of money laundering operations. The study shows the role of internal control procedures in detecting money laundering through electronic programs, and the existence of a system for keeping files and records Money laundering The researcher used the descriptive analytical approach, which is based on the collection of information on the main elements of the study, analysis and interpretation in order to build the theoretical framework for them based on the audit literature and instructions of the Central Bank and commercial banks on internal control of money laundering operations, which dealt with the subject of internal control systems, and anti-laundering law Funds and control measures related to combating money laundering. Through the theoretical framework, a questionnaire was designed on the application of internal control procedures and its relation to combating money laundering operations and distribution to the study population which includes 14 Jordanian banks, with 3 questionnaires for each bank for both internal and external auditors and head of anti-money laundering unit in a bank. The study concluded that it is important to apply the internal control procedures to a high degree among respondents to the questionnaire in preventing and detecting money laundering operations in Jordanian banks